2017
DOI: 10.1093/jac/dkw559
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial resistance inStaphylococcus pseudintermediusand the molecular epidemiology of methicillin-resistantS. pseudintermediusin small animals in Finland

Abstract: Objectives: To investigate antimicrobial susceptibility in Staphylococcus pseudintermedius and the occurrence of methicillin-resistant S. pseudintermedius (MRSP), to explore the molecular structure of the MRSP population and to analyse risk factors for MRSP.Methods: Susceptibility data for clinical S. pseudintermedius isolates in 2011–15 were analysed using WHONET. All MRSP isolates in 2010–14 (n = 362) were typed using PFGE. Representative isolates (n = 87) of clusters were analysed using MLST and staphylococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 40 publications
9
30
1
Order By: Relevance
“…Previous data show that the MRSP carriage rate is higher (9%) in these patients than in low-risk patients i.e. the general Finnish dog population (3%) [ 37 , 40 , 41 ]. There is no reason to expect that the MRSP carriage rate would be higher in the non-screened patients in our study than in the general population.…”
Section: Discussionmentioning
confidence: 98%
“…Previous data show that the MRSP carriage rate is higher (9%) in these patients than in low-risk patients i.e. the general Finnish dog population (3%) [ 37 , 40 , 41 ]. There is no reason to expect that the MRSP carriage rate would be higher in the non-screened patients in our study than in the general population.…”
Section: Discussionmentioning
confidence: 98%
“…MRSP-ST71 is the major clone in Europe [ 2 , 3 ], and there are already few descriptions of this genetic lineage in healthy dogs in Spain [ 18 ]. However, recent studies have reported a downward trend in the prevalence of the MRSP-ST71 lineage among companion animals in northern Europe [ 11 , 19 ] and France [ 3 ]. The MRSP-ST258 lineage, which was detected in this study in 2009, seems to be replacing MRSP-ST71 in these countries [ 11 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRSP is becoming a major pathogen in veterinary hospitals across the world and is difficult to treat as many MRSP isolates are also MDR 61 . Global studies of MRSP carriage in healthy animals report highly varied observations, ranging from approximately 2% to 50% prevalence although surveillance data is limited 62,63 .…”
Section: Discussionmentioning
confidence: 99%